The Financing of Bulgarian Political Advertising in the Media (2003 – 2018) - Manolov, Georgi (Research Papers, 2019)
This article analyzes the money spent by the Bulgarian parties during the election campaigns and the institutional advertising in the media during the period 2003 – 2018. The purpose of the study is to examine public funding of state institutions, and the task is to track the cost of the so- „Institutional advertising“ and the different funds invested in various electronic and printed media. Thus, the fundamental problem of the public funding of Bulgarian political parties is based on the understanding of the essence of political advertising. Specific results are given in the funding of the parties and the media in Bulgaria, which is supported by empirical material. The relevant conclusions drawn from the factual data, as well as some recommendations for improvement of party financing in the country, were also made. The limitations of the study range over a 15-year period (2003 – 2018). The value of the development is characterized by the fact that this problem is one of the first to be analyzed in Bulgarian political science.